A mathematical anxiety scale instrument for junior high school students - Rosyita Anindyarini; Supahar Supahar (Journal of Education and Learning (EduLearn), 2019)
Anxiety becomes one of the psychological symptoms that can appear in every student while solving mathematics problems. Anxiety cannot be denied to be one factor that affects students’ learning outcomes and interest in mathematics. Therefore, teachers should concern on this matter in order to decide the appropriate learning strategy. However, there is no instrument to measure the level of students’ anxiety towards mathematics, especially for junior high school students. For that reason, this research aims to: 1) design the construct of math anxiety scale instrument, 2) find out the validity of the instrument. This research used Research and Development method to develop and validate the product which is in the form of a questionnaire. The analysis techniques used V Aiken for content validity, EFA for construct validity, and Cronbach’s Alpha for the reliability. The results of this research showed that the instrument was valid and reliable because it met the criteria for validity and reliability. In conclusion, the instrument is valid to measure the junior high school students’ math anxiety level.